Improving Performance of Karawang Civil Servant (ASN) West Java Province - Rismayadi, Budi; Maemunah, Mumun (International Review of Management and Marketing, 2018)
This research aims to examine and obtain the empirical evidence of organizational climate influence and organizational commitment to the performance of ASN Government in Karawang Regency West Java Province, either partially or simultaneously. The population in this research is the civil servant (ASN) in the Government Environment Karawang Regency regional. The research method was used in this research is descriptive survey method and explanatory survey with sample size using rule 1 : 5 for amount 200 respondents, and data analysis method used is SEM (Structural Equation Modeling). Based on the results of the research, the findings as follows: Organizational climate and organizational commitment, partially or simultaneously, have a positive and significant influence on the performance of civil servant with the influence of 55% meanwhile the remaining 45% influenced by other factors, but partially the most dominant organizational climate influential on the performance of civil servants. The results also show that the most dominant dimension in measuring organizational climate are on support and reward. While the dimension of continuous commitment is the dominant dimension in measuring organizational commitment and reliability (reliability) is the most dominant dimension in measuring the performance of civil servants. Keywords: Organizational Climate, Organizational Commitment, ASN' Performance JEL Classifications: J0